Analisis User Satisfaction dan Usability terhadap Efektivitas Penggunaan Website SIGAPKL dalam Pelaksanaan Praktik Kerja Lapangan (PKL) Siswa Kelas XII di SMKN 2 Padang - Jannah, Mutiara Miftahul; Irfan, Dedy (Lembaga Yasin AlSys, 2025)
The implementation of industrial work practice (PKL) at SMK Negeri 2 Padang has been supported by the SIGAPKL website as a web-based information system; however, its effectiveness is influenced by users’ perceptions of satisfaction and ease of use. This study aims to analyze the effect of user satisfaction and usability on the effectiveness of the SIGAPKL website. An associative quantitative method was employed, using multiple linear regression analysis on a sample of 80 respondents comprising students and PKL supervising teachers. The results show that both user satisfaction and usability have a significant influence, both partially and simultaneously, on the effectiveness of SIGAPKL use, contributing 90.9% to the variance. User satisfaction emerged as the dominant factor, while usability still requires improvement to optimize the system’s support for PKL implementation.